The Mediating Effect of Corporate Innovation on the Relationship Between Gender Diversity and Firm Performance - Bouchmel, Imen; El Ouakdi, Jihene; Ftiti, Zied; Louhichi, Waël; Omri, Abdelwahed (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
This study investigates the mediating effect of corporate innovation on the relationship between gender diversity in top management and firm performance. Using panel data from French firms listed in the SBF120 index (2013-2017), Generalized Method of Moments (GMM) regressions revealed that the presence of woman on the board and the executive committee positively and significantly influences both corporate innovation and firm performance, and innovation mediates the relationship between gender diversity and firm performance. We conclude that gender diversity in the strategic level improves the firm’s decision-making process, facilitating the initiative to innovate.